Potret Bentuk dan Strategi Eksistensi Kemandirian Perempuan dalam Novel Jalan Bandungan karya NH Dini - Afrodhita; Hasanuddin WS, Hasanuddin WS (Universitas Negeri Padang, 2024)
This research is written to explain the portrait of the form and strategy of the existence of women's independence in the novel Jalan Bandungan by NH Dini. This research uses literary research with qualitative research and descriptive method. The data in this study are in the form of words, phrases, clauses, or sentences that describe the forms and strategies of the existence of women's independence in the novel Jalan Bandungan by NH Dini using theoretical studies of existentialist feminism. The findings of this research include the forms and strategies of the existence of women's independence as follows. (1) Forms of existence of women's independence, namely, (a) exist in themselves, (b) exist for themselves, (c) exist for others. (2) Strategies for the existence of women's independence, namely, (a) women can work, (b) women can become an intellectual, (c) women can achieve socialist transformation of society, (d) women can reject their Otherness.